The Influence of Virus Infection on the Extracellular pH of the Host Cell Detected on Cell Membrane - Liu, Hengjun; Maruyama, Hisataka; Masuda, Taisuke; Honda, Ayae; Arai, Fumihito (Frontiers in Microbiology, 2016)
Influenza virus infection can result in changes in the cellular ion levels at 2–3 h post-infection. More H+ is produced by glycolysis, and the viral M2 proton channel also plays a role in the capture and release of H+ during both viral entry and egress. Then the cells might regulate the intracellular pH by increasing the export of H+ from the intracellular compartment. Increased H+ export could lead indirectly to increased extracellular acidity. To detect changes in extracellular pH of both virus-infected and uninfected cells, pH sensors were synthesized using polystyrene beads (ϕ1 μm) containing Rhodamine B and Fluorescein isothiocyanate (FITC). The fluorescence intensity of FITC can respond to both pH and temperature. So Rhodamine B was also introduced in the sensor for temperature compensation. Then the pH can be measured after temperature compensation. The sensor was adhered to cell membrane for extracellular pH measurement. The results showed that the multiplication of influenza virus in host cell decreased extracellular pH of the host cell by 0.5–0.6 in 4 h after the virus bound to the cell membrane, compared to that in uninfected cells. Immunostaining revealed the presence of viral PB1 protein in the nucleus of virus-bound cells that exhibited extracellular pH changes, but no PB1 protein are detected in virus-unbound cells where the extracellular pH remained constant.